2002
DOI: 10.1002/hon.700
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N‐telopeptide levels in multiple myeloma patients, correlation with Tc‐99m‐sestaMIBI scintigraphy and other biochemical markers of disease activity

Abstract: Urinary cross-linked N-telopeptide of type I collagen (NTx) has been reported to be a sensitive and specific marker of bone resorption in multiple myeloma (MM). In this study, we measured the levels of NTx in 30 newly diagnosed MM patients and 25 controls. We examined its association with the overall score of skeletal involvement measured by Tc-99m-MIBI scintigraphy and other biochemical markers of bone disease (tumour necrosis factor a (TNF-a), serum calcium and creatinine). We further studied the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Several studies speculated on the possible prognostic impact of 99mTc‐MIBI scintigraphy for MM patients (Pace et al , 2001, 2005a,b, 2006; Alexandrakis et al , 2002, 2003; Athanasoulis et al , 2003). Alexandrakis et al (2002) first investigated the 99mTc‐MIBI potential predictive value in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies speculated on the possible prognostic impact of 99mTc‐MIBI scintigraphy for MM patients (Pace et al , 2001, 2005a,b, 2006; Alexandrakis et al , 2002, 2003; Athanasoulis et al , 2003). Alexandrakis et al (2002) first investigated the 99mTc‐MIBI potential predictive value in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…Tc‐99 sestamibi (99mTc‐MIBI) scanning is a nuclear method used to detect a variety of malignant tumours, including sarcomas, lung, thyroid, breast and brain cancer (Alonso et al , 1998; Maurea et al , 1998; Balleari et al , 2001; Svaldi et al , 2001). Recently, several preliminary studies have shown that 99mTc‐MIBI is also actively concentrated in myeloma tissue, identifying sites of active myeloma disease and bone lesions with both high sensitivity and specificity (Adams et al , 1996; Tirovola et al , 1996; Pace et al , 1998; Di Gennaro et al , 1999; Fisher et al , 2000; Alexandrakis et al , 2001, 2003; Balleari et al , 2001; Fonti et al , 2001; Svaldi et al , 2001; Ak et al , 2003; Alper et al , 2003; Mileshkin et al , 2004; Pace et al , 2005a).…”
mentioning
confidence: 99%
“…65 Urinary NTX also correlated with the overall score of skeletal involvement as measured by Tc-99m-MIBI scintigraphy and bone marrow infiltration by plasma cells. 66 Coleman et al showed in 210 MM patients that high or intermediate urinary NTX correlated with an increased risk for SRE development compared with low NTX values (risk ratio (RR) 2.25, P ¼ 0.032 and RR 1.75, P ¼ 0.016, respectively). 57 High NTX values also correlated with a three-fold increased risk for developing a first SRE (Figure 2), whereas there was also a trend toward increased risk for progression of osteolytic lesions in the high NTX group (P ¼ 0.08).…”
Section: Markers Of Bone Remodeling In Myeloma Bone Diseasementioning
confidence: 99%
“…We and others have shown that there is an enhancement of osteoclastic activity in MM patients (3,4,20). This process is mediated by factors produced locally by malignant and non-malignant cells in the microenvironment of bones.…”
Section: Discussionmentioning
confidence: 84%
“…Skeletal morbidity in MM correlates well with the degree of plasma cell infiltration (3,4). The progression of the disease involves the production by the tumor cells of a specific class of extracellular matrix-degrading metalloenzymes, including matrix metalloproteinase (MMP)-9, a 92-kDa type IV collagenase (5,6).…”
Section: Introductionmentioning
confidence: 99%